LINGUAPRAGMATIC STRUCTURE OF COMMAND SPEECHES (on the example of English and Uzbek languages) - Khusanova Hulkar Shamsiddinovna; Khasanova Nasiba Shovqiyevna (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2022)
This article discusses the meaning of command sentences and how speech acts serve as the basis of pragmatics and is divided into five main groups. The command is given in examples from Uzbek and English works on the meaning of sentences in suggestive, requisitive, perspective groups.